Elastic Properties of Woven Fabric CFRP Composites - Sim Yee, Lee; Ahmad, Hilton; Supar, Khairi (International Journal of Engineering and Technology, 2019)
Synthetic fibers such as carbon fibers are widely used as reinforcing materials, to combined with matrix system to produce a high-performance composite material in industrial sectors. Elastic properties of composites are highly dependent upon various factors such as fiber types, fiber orientation, and composite coupon thickness. The elastic properties of twill weave carbon fiber reinforced polymer (CFRP) composite plate was investigated in experimental frameworks. This paper is to determine the mechanical properties and failure mode of CFRP composite plates. The effects of lay-up orientations and coupon thickness were concerned in current study as specified in testing series. Generally, all CFRP coupons failed and breaks within its gauge length. Cross-ply and thicker coupons demonstrates greater strength than quasi-isotropic lay-up counterparts due to larger 0Ëš plies volume fiber fraction.Â Â Â